2022
DOI: 10.5603/cj.a2020.0057
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenaline induced Takotsubo syndrome: Histopathological analyses of female rat hearts

Abstract: Background: Takotsubo syndrome (TTS) is a stress-induced disorder affecting mostly postmenopausal women. The aim of the study was to evaluate isoprenaline (ISO) dependent female rat model and histopathological characteristics in TTS. Methods: Forty-nine Sprague Dawley female rats, 12 weeks old, were injected intraperitoneally with a single dose of ISO at doses 50 (n = 8), 75 (n = 6), 100 (n = 3), 150 (n = 27) and 200 (n = 5) mg/kg body weight (bw). The control group (n = 6) was injected with physiological sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
(46 reference statements)
2
3
0
Order By: Relevance
“…We have also observed relatively lower plasma concentrations of TnI when compared with other studies of ISO-induced myocardial injury. Our histopathological analysis, in agreement with other studies of experimental animal models and clinical cases of TTS, showed only the presence of focal injury of cardiomyocytes scattered between normal cardiomyocytes, therefore the area of myocardial necrosis was relatively small [21,26,63]. A hypothetical mechanism that may be responsible for the lower plasma concentration of TnI in TTS is the dominance of the programmed type of cardiomyocyte cell death.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We have also observed relatively lower plasma concentrations of TnI when compared with other studies of ISO-induced myocardial injury. Our histopathological analysis, in agreement with other studies of experimental animal models and clinical cases of TTS, showed only the presence of focal injury of cardiomyocytes scattered between normal cardiomyocytes, therefore the area of myocardial necrosis was relatively small [21,26,63]. A hypothetical mechanism that may be responsible for the lower plasma concentration of TnI in TTS is the dominance of the programmed type of cardiomyocyte cell death.…”
Section: Discussionsupporting
confidence: 90%
“…The current study is a continuation of our previous reports regarding a female rat model of TTS, where we observed apoptosis in cardiomyocytes 24 h after ISO administration and presence of mild fibrosis, a characteristic feature of TTS, during both the acute and recovery phases [13,26]. To the best of our knowledge, this is the first study showing the activation of necroptosis and pyroptosis pathways in the rat model of ISO-induced TTS.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Of note, the isoprenaline (ISO)-induced female TTS rat model needs a higher triggering dose and has a lower mortality than that of male TTS rats [190]. This may be related to the fact that estrogen has a vasodilator effect through the induction and activation of endothelial nitric oxide synthase, and the reduction of estrogen may interfere with coronary microcirculation by indirect action on the nervous system and by direct action on the heart vessels [119,187].…”
Section: Animal Models and Mechanistic Studiesmentioning
confidence: 99%
“…The animal models of TTS are mainly based on monkeys, rabbits, rats and mice, which can be used to simulate TTS to a certain extent through immobilization, repeated intravenous infusion of an epinephrine overdose, vagal stimulation, intraperitoneally isoprenaline and other methods [152][153][154][182][183][184][185][186][187][188][190][191][192][193][194][195][197][198][199][200][201][202][203][204][205][206]. Many live-stranded cetaceans and terrestrial wildlife experienced capture myopathy, which was similar to TTS [207,208].…”
Section: Animal Models and Mechanistic Studiesmentioning
confidence: 99%